Reengineering in managerial system of competitiveness of enterprise on international level - Biliavskyi , V. M. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2018)
In connection with European integration processes in Ukraine, the operational activity of the enterprise is considered as a complex of measures for the coordination of its production and sales activities with the requirements of world markets. There is an actual need for forecasting the development of economic ties, the analysis of operational activities, the study of foreign markets and the adoption of operational management decisions to enhance their own competitiveness domestic enterprises. The latter point predetermines the need to study, justify and apply the concept of reengineering in the management system of domestic enterprises and use its results to gain competitive advantages, increase the efficiency of functioning and consolidation of positions in the markets. As a result, most enterprises are increasingly using reengineering as a tool for improving the competitiveness of enterprises. Thus, the purpose of this work is to analyze the concept of reengineering of business processes in the system of management of international competitiveness of the enterprise and to identify ways to increase the efficiency of its work. The author substantiates the essence of the theoretical aspects of the formation of the concept of reengineering in the managerial system of the international competitiveness of the enterprise; the conducted analysis has shown that the effective application of these aspects can lead to an increase of productivity of the enterprise. The main requirements of successful operation of the enterprise on foreign markets are determined, which allows the top management of the airline to take measures regarding the formation and implementation of an effective strategy for the development of the competitiveness of the enterprise at international level. The business processes of strategic management are schematically reflected by an international competitiveness of enterprises, that correspond to each of the given constituents, envisaging realization of cardinal changes of structure and functionality of subdivisions of enterprises. The main projects and directions of economic activity of PJSC «Ukraine International Airlines» (UIA) are analysed, which allows top managements to take measures regarding the construction of an effective organizational structure of the enterprise management. The above-mentioned approach to the study of the concept of reengineering in the system of managing the international competitiveness of an enterprise is possible to consider as one of the examples of searching for alternative ways of solving a problem, and which can be used to create objective prerequisites and methodological basis of research on this issue.